The hermit сharacter as a new type of character in realistic prose by Maxim Gorky - Strokina, Svetlana (2021)
1922-1924 was a fruitful period of Maxim Gorky's literature work. It is related to searching a new art form. The cycle “Stories of 1922-1924” is an expressive example of “new prose”. For the first time, the hermit character appeared in the cycle “Stories of 1922-1924”. From the point of view of generally recognized morality and the Church, the new type of character is ambiguous. It is characterized by both sinfulness and holiness.